The evolution of China’s approach to Africa: towards a community with a shared future for mankind - An, Nan (Journal of the Belarusian State University. International Relations, 2026)
This article examines the historical evolution of China’s engagement with African states and its progression towards building a community with a shared future for mankind. The analysis focuses on two main questions: how China’s approach to Africa has changed over time, and how the shared future vision has been advanced in practice on the continent. The study identifies four stages in the evolution of China – Africa relations: political support and assistance, economic cooperation and joint development, institutionalised cooperation, and the current focus on building of China – Africa community with a shared future. The article further shows that this vision has been advanced in Africa primarily through regional China – Africa cooperation and only subsequently through bilateral relations. This process has already produced substantial results in the political, economic and social spheres. Ultimately, the movement of China and Africa towards a shared future represents an important practical contribution to the consolidation of the Global South and to strengthening its role in global governance.
Keywords: China – Africa relations; evolution of the China’s approach to Africa; community with a shared future for mankind; Forum on China – Africa cooperation; Global South